Interpretation of Humanistic Ideas in the Views of the Mystic Mashrab (Eurasian Journal of Humanities and Social Sciences, 2022)
In this scientific article, the study of the humanist ideas in the socio-philosophical views of the Uzbek poet and thinker, mystic and Sufi Mashrab, the universal views of the poet such as humanity, justice, and patriotism were analyzed.